Application of Dispersed Particle Gel to Inhibit Surfactant Adsorption on Sand. Issue 4 (10th May 2017) - Wu, Yining; Chen, Wenxia; Hu, Mei; Dai, Caili; Zhao, Mingwei; He, Long
Abstract: This article highlights an efficient and cost‐effective additive‐dispersed particle gel (DPG) to reduce surfactant adsorption on sand. Indoor experiments were conducted to study the effect of DPG on static adsorption and dynamic adsorption of the surfactant. The static adsorption data were evaluated using different isotherm models and the Redlich–Peterson isotherm matched the best. Results showed a significant inhibition of surfactant adsorption in the presence of DPG. The dynamic adsorption of SDS on sand decreased to 0.78, 0.68 and 0.61 mg/g compared with original value of 1.17 mg/g by adding 0.1, 0.2 and 0.3 wt% DPG particles, respectively. This study suggests that DPG can inhibit the adsorption of surfactant on sand effectively.